Robotic sailing proceedings of the 4th International Robotic Sailing Conference - International Robotic Sailing Conference 2011 Lèubeck, Germany); Schlaefer, Alexander; Blaurock, Ole.; SpringerLink (Online service). (Berlin Springer Berlin Heidelberg, 2011)
While sailing has a long tradition, both as a means of transportation and as a sport, robotic sailing is a fairly new area of research. One of its unique characteristics is the use of wind for propulsion. On the one hand, this allows for long range and long term autonomy. On the other hand, the dependency on changing winds presents a serious challenge for short and long term planning, collision avoidance, and boat control. Moreover, building a robust and seaworthy sailing robot is no simple task, leading to a truly interdisciplinary engineering problem. These proceedings summarize the state of the art as presented at the International Robotic Sailing Conference 2011. Following an overview of the history of autonomous sailing a number of recent boat designs is presented, ranging from small one-design boats to vessels built to cross the Atlantic Ocean. Subsequently, various aspects of system design and validation are discussed, further highlighting the interdisciplinary nature of the field. Finally, methods for collision avoidance, localization and route planning are covered.
Part I Introduction -- Part II Robotic Sailboats -- Part III System Development -- Part IV Collision Avoidance -- Part V Localization and Route Planning.
Electronic reproduction.
Keywords: Autonomous robots -- Congresses; Sailing -- Technological innovations -- Congresses; Electronic books